ANALISIS POLA SALURAN PEMASARAN USAHA TEMPE INDUSTRI RUMAH TANGGA DI KELURAHAN GUNTUNG PAIKAT KOTA BANJARBARU - Zulipah Mahdalena; Fadli Yannur (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research was conducted on Guntung Paikat village at Banjarbaru district, on 26 April until 26 Juni 2018. This study aims to determine the market channels and analyze the margins of tempeh. The Method used was.survey method and porposive samping technique Data obtained through interview technique to marketing actors (Farmer, wholesalers and retailers) and analyzed descriptively. Results of this stusy showed that the tempeh marketing channels on Guntung Paikat village consists of several types that are I, II and III. Marketing Margin for each Tempeh of marketing channels I, II and III, respectively are Rp.3000Rp.2000,-, and Rp.0 The Highest farmer’s share received by tempeh producers is on channel II (60%) and the lowest is on channel 1 (50%). The Average Farmer’s share is 55 %. Keywords : tempeh, marketing channels , marketing margin, farmer’s share, guntung paikat village